Penetralan Air Asam Tambang Menggunakan Campuran Kapur Tohor Dan Tawas Untuk Memenuhi Baku Mutu Lingkungan Pada Parameter pH Dan TSS Di KUD Sinamar Sakato - Yolanda, Melfa; Hadiyansyah , Dian; Rahmi , Hisni; Nelvi, Afni; Marlina Amsya, Riam; Juniah , Restu; Fadhly, Ahmad (Jurnal Teknologi Infrastruktur, 2023)
The results of observations of acid mine water in KUD Sinamar Sakato is known by the presence of water in the settling pond has a pH of 5.2 besides that there is also the presence of brownish turbid wastewater. The purpose of the study was to analyze the quality of acid mine water after the addition of a mixed dose of alum and quicklime, analyze the amount of dose requirement of the mixture of alum and quicklime and the costs required to neutralize the acid mine water. The primary data needed are the pH of the water, the value of TDS. The quality of acid mine water after the addition of a dose of a mixture of alum and quicklime to the KUD Sinamar Sakato has met environmental quality standards for pH and TSS with a mixed dose of 0.25 g/l of quicklime plus 0.5 g/l of alum. The amount of need to neutralize acid mine water for field-scale doses required of alum mixture as much as 79.92 kg d an increase of 399.6 kg of quicklime per day. The cost required in neutralizing acid mine water with a mixed dose of alum and quicklime for 1 day for a total of Rp 4,075,920.